Organized crime: causes and consequences - Lombardo, Robert M. (Criminal justice, law enforcement and corrections, 2019)
"This book studies the causes and consequences of organized crime drawing on research from around the world including the countries of Colombia, China, Ireland, Italy, Japan, Mexico, Russia, Sweden and the United States. It also includes a discussion of transnational crime and several other key theoretical topics. One important issue examined in this text is the difference between the terms organized crime, international organized crime and transnational organized crime, an often-confusing subject. As the title indicates, one of the goals of this volume is to identify the causes of organized crime. Working independently, the contributing authors have identified similar characteristics as the causes of organized crime no matter the country, culture or time period. For those teaching organized crime at the university level, this book will be a valuable resource. It provides both an in-depth and analytical look at the world's most powerful and persistent criminal organizations. Taking an interdisciplinary approach, this book contains both qualitative and quantitative research. The works are all original, there are no reprinted chapters in this volume. This text not only provides historical background on the world's most powerful criminal organizations, but also challenges common assumptions about the organization of these infamous groups. This is no 'guns and garlic' book but contains in-depth sociological analyses of current trends in organized crime, one that should be of interest to government officials and those responsible for setting public policy. While this book will be of interest to the serious student, non-academics and casual readers alike will also be interested in the work presented here. It provides a fascinating look at a serious social problem, one that is forever evolving and will continue to challenge the international community"--